ANALSIS MODEL PEMBELAJARAN IMAM AL-GHAZALI DALAM KITAB IHYA ULUMUDDIN - Fazillah, Fazillah (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Agama Islam Jamiatut Tarbiyah Lhoksukon, 2024)
The flow of globalization makes many people and even educators do not understand the theories and educational concepts of previous muslim scholars and philosophers, for example the learning models of Imam Al-Ghazali in the book Ihya Ulumuddin. Formulation problems: 1. What is the learning model of Imam Al-Ghazali in the Ihya Ulumuddin book? 2. How is the relevance of Imam Al-Ghazali’s learning model of Ihya Ulumuddin in current context? The purpose of this study is to analyze the learning model of Imam Al-Ghazali in Ihya Ulumuddin with the contemporary context. This is qualitative research (library research) with a pedagogical approach. The nature of research is descriptive, the data collection served with documentation and techniques content analysis. The results of the study: 1. The learning model of Imam Al-Ghazali in Ihya Ulumuddin is the learning model of tahshil wa waqfah, istikhraju wa aktsaru himam, ikhtilafu bi hal and ‘ilm al-mu’amalah wa al-riyadhah. 2. Imam Al-Ghazali’s learning model in ihya ulumuddin is relevant to contextual, cooperative, problem-based and active learning models. Imam Al-Ghazali’s learning model mentions the steps to discuss and guide students. This learning model is relevant to be applied in this contemporary era.